Inflammation induced by inactivated Aeromonas hydrophila in Nile tilapia fed diets supplemented with Saccharomyces cerevisiae - Reque, Valeska Regina [UNESP]; Engracia de Moraes, Julieta Rodini [UNESP]; de Andrade Belo, Marco Antonio [UNESP]; de Moraes, Flavio Ruas [UNESP] (Elsevier B.V., 2010)
The inflammatory response and hernatological parameters among Nile tilapia (Oreochromis niloticus) supplemented with Saccharomyces cerevisiae were evaluated six and 24 h after inoculation with inactivated Aeromonas hydrophila into the swim bladder. Six groups were formed (n = 10 each): G1 was treated with non-supplemented feed+injection with 0.65% saline solution; G2 with non-supplemented feed+ inoculation with A. hydrophila: G3 with feed containing 2% yeast+ injection with saline; G4 with feed containing 2% yeast + inoculation with A. hydrophila: G5 with feed containing 0.3% cell wall + injection with saline: and G6 with feed containing 0.3% cell wall + inoculation with A. hydrophila. In the groups inoculated with bacteria, the responses were more intense (P<0.05) than in those injected with saline. The groups receiving supplement that were inoculated with A. hydrophila accumulated a greater total number of cells at the lesion site (P<0.05) than did the non-supplemented groups, after six and 24 h. The groups receiving cell wall presented greater total accumulation of cells (P<0.005) that did those receiving yeast. The differential count showed that there were significantly greater number of thrombocytes (P< 0.05) and lower number of neutrophils, macrophages and lymphocytes (P<0.05) in the groups that received supplement, after 6 and 24 h, in relation to the non-supplemented groups. The values in the erythrocyte count, hemoglobin concentration and blood measurement indices did not differ statistically. The variation in circulating thrombocyte and leukocyte counts suggests that the inflammatory stimulus caused recruitment from reserve compartments to the blood. The groups that received yeast or yeast cell wall supplements presented increased nonspecific acute inflammatory response, thus suggesting that this has a beneficial effect on the immunological defense system. Published by Elsevier B.V.
Keywords: Inflammation; Oreochromis niloticus; Saccharomyces cerevisiae; Immunostimulant; Aeromonas hydrophila